IMPLEMENTATION OF CASH FLOW AS A MEASURING TOOL IN PREDICTING FUTURE NET INCOME : (CASE STUDY AT KEDAI NYOBIAN 8 DAILY PERIOD SEPTEMBER – OCTOBER 2020) - Dhea Parlina, Nurhana; Budianto, Erwin (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2021)
In Indonesia, MSMEs are protected and have a legal shield such as the Presidential Decree No. 19 of 1998 and several other regulations. Where at this time, many MSME businesses are starting to grow both on a household and large scale, this includes Culinary Business. Culinary businesses are one of the many MSME that are starting to flourish, both on a domestic and big scale, at present moment. This business is in high demand among teenagers and adults. With a limited budget, this business may be launched at home, and it has a potential future. Therefore, the background behind the realization of Kedai Nyobian 8 which is used as a case study of problems that occur in the operational activities of Kedai Nyobian 8. The purpose of this study is to analyze net income in predicting operating cash flows in the future. The research method used is quantitative method. The population in this study is a case study at Kedai Nyobian 8 with a number of samples in the form of financial statements for September for 30 days. While October for 26 days, hence the total sample is 56 observations. The sampling measurement technique is a case study at Kedai Nyobian 8 using Saturated Sample. Therefore, Kedai Nyobian 8 will be more effective and achieve better results in the future by reducing unnecessary costs and anticipating future earnings in cash flow.